Natural history and developmental trajectories of individuals with disease-causing variants in STXBP1 - Thalwitzer, Kim M.; Driedger, Jan Henje; Xian, Julie; Saffari, Afshin; Zacher, Pia; Bölsterli, Bigna K.; McKeown Ruggiero, Sarah; Sullivan, Katie Rose; Datta, Alexandre N.; Kellinghaus, Christoph; Althaus, Jürgen; Wiemer-Kruel, Adelheid; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Pathogenic variants in STXBP1 are among the major genetic causes of neurodevelopmental disorders. Despite the increasing number of individuals diagnosed without a history of epilepsy, little is known about the natural history and developmental trajectories in this subgroup and endpoints for future therapeutic studies are limited to seizure control. - METHODS: We performed a cross-sectional retrospective study using standardized questionnaires for clinicians and caregivers of individuals with STXBP1-related disorders capturing medical histories, genetic findings, and developmental outcomes. Motor and language function were assessed using Gross Motor Function Classification System scores (GMFCS) and a speech impairment score and were compared within and across clinically defined subgroups. - RESULTS: We collected data of 71 individuals with STXBP1-related disorders, including 44 previously unreported individuals. Median age at inclusion was 5.3 years (IQR = 3.5-9.3) with the oldest individual aged 43.8 years. Epilepsy was absent in 18/71 (25%) of individuals. The range of developmental outcomes was broad, including two individuals presenting with close to age-appropriate motor development. 29/61 (48%) individuals were able to walk unassisted and 24/69 (35%) were able to speak single words. Individuals without epilepsy presented with a similar onset and spectrum of phenotypic features but had lower GMFCS scores (median 3 vs. 4, p < 0.01) than individuals with epilepsy. Individuals with epileptic spasms were less likely to walk unassisted than individuals with other seizure types (6% vs. 58%, p < 0.01). Individuals with early epilepsy onset had higher speech impairment scores (p = 0.02) than individuals with later epilepsy onset. - DISCUSSION: We expand the spectrum of STXBP1-related disorders and provide clinical features and developmental trajectories in individuals with and without a history of epilepsy. Individuals with epilepsy, in particular epileptic spasms, and neonatal or early-onset, presented with less favorable motor and language functional outcomes compared to individuals without epilepsy. These findings identify children at risk for severe disease and can serve as comparator for future interventional studies in STXBP1-related disorders.
Gesehen am 17.07.2023